The Effectiveness of Extracurricular (Qur'an Hadith) in State High School (SMAN) 15 Takengon Binaan Nenggeri Antara - Hermawati Hermawati (Al-Hayat: Journal of Islamic Education, 2021)
Al-Qur'an and Hadith have an important role especially in high school-age children, where very few of them learn and understand the contents of the Qur'an and Hadith. In addition, students do not yet understand the importance of understanding the Qur'an and Hadith for the future. Many of them lack interest, lack parental roles, and an unsupportive environment. This study aims to increase knowledge and understanding related to the Effectiveness of the Additional Lesson Activity (Qur'an) Hadith in the afternoon at SMAN 15 Takengon guided by Tereng Antara. Local policies began to erode with the inclusion of modern culture. For example, many Takengon students spend time playing games in internet cafes so that they do not have time to practice the Koran and the Koran as room decoration, even making antiques that are only displayed in a glass cabinet, never read moreover study it. Reflecting on this, there is great hope for educators to apply the teachings of Al-Qur'an Hadith to all students.